(untitled) (Research, Society and Development, 2020)
In recent years, some SPH codes have become an inherent part of the numerical arsenal of industrial research, development laboratories and academic institutions. SPH’s capacity to deal with issues of varying density and different flows, stems from the fact that its nature is totally Lagrangian. The idea of the method is to follow the fluid through the moving particles, without any mesh restriction. The objective of this work is to model the dynamics of the fluid present in the phenomenon of rupture of dams through the SPH mesh-free numerical method, in addition to comparing the simulated results with labor results. The studies carried out provided subsidies for modeling the dam rupture problem using the SPHysics software (open source), with the SPH methodology, where the method proved to be efficient in the proposed modeling, which becomes evident through the comparison with the labor results , as shown in the results.